Social media and creativity: The moderating role of executive functions - TAN, Joanne Qin Ying (Institutional Knowledge at Singapore Management University, 2019)
Despite the potential for social media to promote creative potential, little is known about this direct relation and the process by which engagement with social media affects the production of creative ideas. This study puts forth a novel application of the Dual-Pathway to Creativity Model (DPCM) to understand the social media-creativity link. The results showed that social media can be used for normative (checking and browsing), interactive (“liking”), and generative (posting photos) purposes. After controlling for pertinent covariates, only normative use was negatively related to the flexibility pathway. When each aspect of executive functions (updating, inhibition, and shifting) was examined as a separate moderator to clarify the conditions under which social media relates to creativity, only working memory significantly moderated the relationship between normative uses and persistence. These results contribute to an initial understanding of how the production of creative ideas is affected by engagement with social media and one’s cognitive ability.